Hepatitis B: Knowledge and attitude of graduating dentists from faculty of dentistry, Sebha University, Libya - Syed Wali Peeran; Syed Ali Peeran; Marei Hamad Al Mugrabi; Khaled Awidat Abdalla; Manohar Murugan; Fatma Mojtaba Alsaid (Wolters Kluwer Medknow Publications, 2017)
Background: Hepatitis B virus (HBV) is a major worldwide cause of acute and chronic liver infection. Dentists, dental students, and their paramedical staff are at a heightened risk of exposure to HBV. Aim: The aim of this study was to assess the knowledge and attitude of the graduating dentist from Faculty of Dentistry, Sebha University (Libya), toward hepatitis B infection. Subjects and Methods: Ninety-nine participants completed the self-administered, structured, pilot-tested close-ended 37-item questionnaire. Results: It was found that the graduating dental students from different study years have similar knowledge and attitude, except for the responses to questions on curriculum, contracting hepatitis B virus (HBV) from patient, vaccination schedule, perception, and treatment modality for HBV-infected patient, where statistically significant difference was noted. Conclusion: The results indicate that there is need to spread greater awareness about risk and seriousness of the HBV infection among the graduating dentists. We recommend that the dental policymaker considers modifying the dental curriculum to include a detailed session of training in areas of universal infection control procedures, handling high-risk patients, combating fear while treating patients, and teaching them to avoid discriminatory behavior beginning in the 3rd year itself.